Secondary Metabolites Phytochemical Analysis of Leaves and Fruit Extract Solanum blumei Nees ex Blume Local - Murniaty Simorangkir; Ribu Surbakti; Tonel Barus; Partomuan Simanjuntak (Pascasarjana Universitas Negeri Medan, 2017)
Abstract: Ranti hitam plant (Solanum blumei Nees ex Blume), Solanaceae family is found in Karo and Dairi, traditionally used as a medicinal plant. The results of phytochemical analysis of extract of S. blumei Nees ex Blume shows that secondary metabolites alkaloids, flavonoids, tannins and saponin are more numerous in the ethanol extract of the leaves than the ethanol extract of the fruit. Quinone is only found in the ethanol extract of the leaves. Phenol is widely available on the ethyl acetate extracts of leaves and fruit.Steroids and triterpenoids are abundant in n-hexane extract and ethyl acetate leaves and fruit as well as the ethanol extract of the leaves. The yield of extract n-hexane, ethyl acetate and ethanol blumei leaves S. Nees ex Blume respectively are 1.76%; 3.17% and 9.95% (w/w). The yield of extract n-hexane, ethyl acetate and ethanol fruit S. blumei Nees ex Blume respectively are 1.21%; 2.50% and 4.09% (w/w). Keywords: phytochemicals, Indonesian, ranti hitam (Solanum blumei Nees ex Blume), medicinal plant